ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH KOTA YOGYAKARTA 2020-2023 - Nansi, Maria Regina; Hidayati, Fika; Susanti, Maria Emiliana Natalia Trisakti; Dewitasari, Rina Putri (Manis: Jurnal Manajemen dan Bisnis, 2025)
The financial ratio analysis in this research is aimed at assessing the financial performance of the Yogyakarta City Government for the fiscal year 2020-2023. The research method used is descriptive-quanitative by utilizing secondary data in the form of Yogyakarta City Regional Government financial reports for 2020-2023, Budget Realization Reports, balance sheets, and Yogyakarta City PAD Recipient Details Reports. Secondary data was obtained through literature studies and published financial reports. This research uses five financial ratios, namely the independence ratio, effectiveness ratio, efficiency ratio, harmony ratio and growth ratio.The analysis results of these five ratios show that the City of Yogyakarta has experienced improvements in several aspects of financial management, especially in the independence and effectiveness ratios. The independence ratio increased from 51% to 67%, indicating a better ability to rely on PAD. The effectiveness ratio is always above 100%, indicating the effectiveness of revenue management. The efficiency ratio is below 100%, indicating efficient use of the budget. The alignment ratio shows an increase in operational expenditure, while capital expenditure remains stable. In conclusion, the City of Yogyakarta has succeeded in maintaining financial stability and budget efficiency, but needs more attention to the allocation of capital expenditure for long-term development.Although financial implementation each year is generally in accordance with planning, budget absorption is less than optimal due to the use of a budget.